Variability in pupil size estimation. Issue 6 (19th May 2006) - Clark, A; Clarke, T N S; Gregson, B; Hooker, P N A; Chambers, I R
Abstract : Background: The clinical estimation of pupil size and reactivity is central to the neurological assessment of patients, particularly those with or at risk of neurological damage. Health care professionals who examine pupils have differing levels of skill and training, yet their recordings are passed along the patient care pathway and can influence care decisions. The aim of this study was to determine if any statistical differences existed in the estimation of pupil size by different groups of health care professionals. Methods: A total of 102 health care professionals working in the critical care environment were asked to estimate and record the pupil size of a series of 12 artificial eyes with varying pupil diameter and iris colour. All estimations were performed indoors under ambient lighting conditions. Results: Our results established a statistically significant difference between staff groups in the estimation of pupil size. Conclusion: The demonstrated variability in pupil size estimation may not be clinically significant. However, it remains desirable to have consistency of measurement throughout the patient care pathway.